2017
DOI: 10.5664/jcsm.6446
|View full text |Cite
|
Sign up to set email alerts
|

Exercise, Occupational Activity, and Risk of Sleep Apnea: A Cross-Sectional Study

Abstract: Structured physical exercise is associated with lower odds for OSA, independently of confounders. Occupational activity does not seem to replace the effects of regular exercise. Compensatory behaviors may be involved in these diverging outcomes. Our results warrant further research about the effect of occupational activity on OSA severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…adjusted odds ratio for moderate to severe OSA, 0.76; 95% CI, 0.59–0.98; Murillo et al., ). A cross‐sectional study of 5,453 Brazilian adults reported that structured physical exercise was associated with 23% lower odds of moderate OSA and 34% lower odds of severe OSA, after adjusting for BMI (da Silva et al., ). All of these studies examined physical activity or exercise, but not CRF, and most studies have examined effects on symptom severity in patients with existing OSA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…adjusted odds ratio for moderate to severe OSA, 0.76; 95% CI, 0.59–0.98; Murillo et al., ). A cross‐sectional study of 5,453 Brazilian adults reported that structured physical exercise was associated with 23% lower odds of moderate OSA and 34% lower odds of severe OSA, after adjusting for BMI (da Silva et al., ). All of these studies examined physical activity or exercise, but not CRF, and most studies have examined effects on symptom severity in patients with existing OSA.…”
Section: Discussionmentioning
confidence: 99%
“…TA B L E 1 Characteristics of 18-year-old men who were or were not subsequently diagnosed with sleep apnea, Sweden, 1969Sweden, -2012 To our knowledge, this is the first study to examine CRF in relation to the risk of sleep apnea. Prior studies have suggested that high physical activity or exercise levels are associated with reduced symptoms and improved outcomes in patients with existing OSA, irrespective of body weight or BMI (Aiello et al, 2016;Iftikhar et al, 2014;Mendelson et al, 2018;Murillo et al, 2016;da Silva et al, 2017). For example, three meta-analyses of small clinical trials reported that exercise training was independently associated with reduced severity of apnea symptoms in patients with OSA (Aiello et al, 2016;Iftikhar et al, 2014;Mendelson et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 7 One confounder in the OSA-exercise association is exercise intensity 8 . In a previous study conducted by our group, exercise was associated with a 34% lower adjusted risk of severe OSA 9 …”
Section: Introductionmentioning
confidence: 94%
“…A considerable proportion of individuals with OSA exercise. It has been reported that 34% of patients with moderate-to-severe OSA exercise regularly, 8 as do 21% of those with severe OSA, 9 indicating the relevance of studying the relationship between OSA and exercise.…”
Section: Introductionmentioning
confidence: 99%